ENSURING THE SAFE USE OF UNMANNED VEHICLES UNDER THE THREATS OF EPIDEMICS AND PANDEMICS IN A MEGAPOLIS: ISSUES OF PUBLIC LEGAL REGULATION - Alexander I. Zemlin; Maria A. Matveeva; Evgeniia V. Gots (Siberian Journal of Life Sciences and Agriculture, 2023)
The purpose of studying the issues of ensuring the safe and efficient use of unmanned vehicles in a megalopolis in the context of the spread of infectious diseases using public regulation tools is to develop, based on the application of methods of systemic legal analysis, evidence-based proposals for improving legislation in the interests of using unmanned vehicles in a megalopolis in order to countering the spread of epidemics and pandemics. The lack of results of scientific understanding of the experience of legal support for the functioning of the transport system of the metropolis in the context of epidemics and pandemics, and, in particular, during the period of countering the spread of the coronavirus infection COVID-19, both in foreign countries and in Russia, seems to be an important negative factor that minimizes the potential of using self-driving cars to reduce cross-contamination opportunities in high-density areas, which undoubtedly include metropolitan areas.